Mobile phone communication on a local are network - Casupanan, Argel Joseph (2006)
Bluetooth technology was developed to unite the worlds of computer and telecommunication. In 1994, Ericsson Mobile Communications investigated the feasibility of a low-power, low-cost radio interface between mobile phones and their accessories. With this goal of Bluetooth technology, this project followed the same line of thought. It integrated Bluetooth technology and VoIP into a system that allows mobile voice calls to be transmitted over a local area network (LAN). Thus, the project provides low-cost, reliable, flexible, and readily available means of communication between mobile phones within a LAN.